Purification and Characterization of an Acetyl Xylan Esterase from Bacillus pumilus - Degrassi, Giuliano (American Society for Microbiology, 1998)
Bacillus pumilus PS213 was found to be able to release acetate from acetylated xylan. The enzyme catalyzing this reaction has been purified to homogeneity and characterized. The enzyme was secreted, and its production was induced by corncob powder and xylan. Its molecular mass, as determined by gel filtration, is 190 kDa, while sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed a single band of 40 kDa. The isoelectric point was found to be 4.8, and the enzyme activity was optimal at 55°C and pH 8.0. The activity was inhibited by most of the metal ions, while no enhancement was observed. The Michaelis constant (K(m)) and V(max) for α-naphthyl acetate were 1.54 mM and 360 μmol min(−1) mg of protein(−1), respectively.